andererseits - Yearbook of Transatlantic German Studies Vol. 7/8, 2018/19 - Donahue, William Collins; Mein, Georg; Parr, Rolf (andererseits - Yearbook of Transatlantic German Studies, 2020)
andererseits seeks to provide a forum for unique and exciting research and reflections on topics related to the German-speaking world and the field of German Studies. Works presented in the publication come from a wide variety of genres including book reviews, poetry, essays, editorials, forum discussions, academic notes, lectures, and traditional peer-reviewed academic articles. In addition, contributions by journalists, librarians, archivists, and other commentators interested in German Studies broadly conceived. By publishing such a diverse array of material, we hope to demonstrate the extraordinary value of the humanities in general, and German Studies in particular, on a variety of intellectual and cultural levels. Contributors to this volume: Yvonne Delhey, Andreas Erb, Bernhard Fischer, Rüdiger Görner, Spencer Hawkins, Steffen Kaup, Selim Özdogan, Hugh Ridley, Gertrud Maria Rösch, Peter Stamm, Wim Wenders, and others.